The lift pool method for isolation of cDNA clones from lambda phage libraries - LeBlanc-Straceski, Janine; Sobrado, Pablo; Betz, Sharon; Zerfas, Julie; Morgan, Karen (Electronic Journal of Biotechnology, 2006)
A PCR based strategy was developed to screen a Xenopus oocyte λgt10 cDNA library. The PCR-based lift pool (LP) method follows the same two tiered strategy as conventional screening of phage libraries by filter hybridization. Two rounds of plating, one at high density to detect the clone, and one at low density to purify the clone to homogeneity, are performed. In the first round, lysates from high density plates, termed plate pools (PP), serve as template for PCR. In the second round, phage particles adhering to plaque lifts of low density plates are washed off nitrocellulose filters to create LPs, which are used as template for PCR. The integrity of the plaques on the low-density plates is preserved. Once a positive LP has been identified, plaques on the corresponding plate are screened individually by PCR. Using isoform specific primer pairs for Xenopus myosin 7a and myosin 1d, two lambda clones were isolated. Subsequent DNA sequence analysis confirmed their identities as myosin isoforms (GenBank accession numbers: DQ100353 and AF540952). This method offers a time saving, cost-effective alternative to other hierarchical pooling strategies for the repeated screening by PCR of an arrayed lambda phage library.